2021
DOI: 10.3390/ijerph18189488
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling of COVID-19 Vaccine Hesitancy in the United States

Abstract: Vaccine hesitancy refers to delay in acceptance or refusal of vaccines despite the availability of vaccine services. Despite the efforts of United States healthcare providers to vaccinate the bulk of its population, vaccine hesitancy is still a severe challenge that has led to the resurgence of COVID-19 cases to over 100,000 people during early August 2021. To our knowledge, there are limited nationwide studies that examined the spatial distribution of vaccination rates, mainly based on the social vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 48 publications
2
53
2
Order By: Relevance
“…A recent publication regarding COVID-19 vaccine hesitancy in the US, showed that the geospatial disparity of vaccine hesitancy is highly correlated with socio-economics covariates (eg, ethnicity, income, etc), and the authors advocated the role of policymakers, community groups, and faith leaders in increasing public trust to reduce vaccine hesitancy. 164 Vaccine hesitancy in some European countries were linked to concerns about safety and efficacy besides the speed with which these vaccines were developed. 138,139,142 The conspicuous pattern of declining rates of COVID-19 vaccine acceptance observed in different countries in this review (Australia, Ethiopia, France, Japan and Jordan), can appear antithetical considering the accumulating evidence of safety and efficacy of the currently approved COVID-19 vaccines.…”
Section: Dovepressmentioning
confidence: 99%
“…A recent publication regarding COVID-19 vaccine hesitancy in the US, showed that the geospatial disparity of vaccine hesitancy is highly correlated with socio-economics covariates (eg, ethnicity, income, etc), and the authors advocated the role of policymakers, community groups, and faith leaders in increasing public trust to reduce vaccine hesitancy. 164 Vaccine hesitancy in some European countries were linked to concerns about safety and efficacy besides the speed with which these vaccines were developed. 138,139,142 The conspicuous pattern of declining rates of COVID-19 vaccine acceptance observed in different countries in this review (Australia, Ethiopia, France, Japan and Jordan), can appear antithetical considering the accumulating evidence of safety and efficacy of the currently approved COVID-19 vaccines.…”
Section: Dovepressmentioning
confidence: 99%
“…[15, 48]) and aggregated level in England and internationally (e.g. [10, 49]). Additionally, in line with [50], who found that people with a physical health condition before the pandemic were more likely to take up the offer of vaccination, we also highlighted that areas more aware of the health risk due to COVID-19 are characterised by higher uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Using a multiscale geographically weighted regression model, Mollalo and Tatar [45] analyzed spatial heterogeneity of COVID-19 full-vaccination rates across all counties in the continental US using social vulnerability index data. They found that the model explains over 79% of the variance of vaccination rate based on per capita income and minority (%) (with positive impacts), and age 17 and younger (%), mobile homes (%), and uninsured people (%) (with negative effects).…”
Section: Risk Analysismentioning
confidence: 99%
“…Marcec, Majta[31] D, R 3 Mollalo and Tatar[45] D, N, M 5indicates the theme used in the study. * D-Descriptive; R-Exploratory; N-Explanatory; M-Modeling.…”
mentioning
confidence: 99%